Realization of a magnetic mirror for cold atoms - Roach,TM; Abele,H; Boshier,MG; Grossman,HL; Zetie,KP; Hinds,EA (Physical Review Letters, 1995)
We have demonstrated that cold atoms can be retroflected from a ferromagnetic surface by the Stern-Gerlach effect. When the surface is magnetized periodically, the reflectivity for suitably polarized atoms is (948)% and the reflection is specular. A demagnetized surface is also highly reflecting but the reflections are diffuse. These magnetic processes are of interest for atom optics because they permit the manipulation of cold atoms without the use of laser beams. In our experiments, Rb atoms released from a magneto-optic trap (MOT) fall under gravity until they are reflected, after which they are recaptured in the MOT. Multiple bounces of these atoms have been studied for times up to 600 ms. © 1995 The American Physical Society.